TECHNOLOGY TO DEVELOP STUDENTS' TECHNICAL THINKING IN TECHNOLOGY CLASSES (World Bulletin of Social Sciences, 2022)
This article discusses technologies for the development of students' technical thinking in technology lessons, innovative teaching technologies, robotics, modeling, design, and the formation of engineering skills.